A 90nm Process Technology Indoor Artificial Light Energy Harvesting for Battery Recharging and Wireless Sensor Nodes Application - Mocorro-Overstreet, Chinet; Sabarillo, Rochelle (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2022)
A photovoltaic energy harvesting system is designed in a 90nm CMOS technology to improve its efficiency and harvesting capability. The system utilizes a 500mV single unit solar cell operating under room lighting illumination. The PV output voltage supplies the input stage of the whole system including the bootstrapped ring oscillator and self-Vth-cancellation differential rectifier, whose output frequency is 27MHz, which in turn generates the supply for the low-dropout regulator (LDO) and the charging circuit of the rechargeable NiMH battery of the output stage. The regulated output voltage from the LDO is equal to 1V with load current ranging from 50 μA to 300μA which is suitable for wireless sensor networks application. Utilizing the downscale technology with a reduced low-threshold voltage transistors results to a more efficient design architecture, achieves high-speed performance in terms of channel conduction, thus, minimizes the power consumption and extend battery life.